The Effect of Location, Facilities, and Service Quality on Guest Satisfaction at Wimarion Hotel Semarang - Choirul Anwar; Zahrina Nabila Abidin (International Journal of Travel, Hospitality and Events, 2026)
This study examines the influence of location, facilities, and service quality on guest satisfaction at Wimarion Hotel Semarang. The rapid growth of tourism in Semarang has intensified competition among hotels, making guest satisfaction a key factor in maintaining competitiveness. This study aims to analyze the partial and simultaneous effects of location, facilities, and service quality, as well as to determine the most dominant variable affecting guest satisfaction. A quantitative approach was employed using primary data collected through questionnaires distributed to 95 guests who stayed at Hotel between March and May 2025. The sampling technique used was purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 21. The analysis included validity and reliability tests, classical assumption tests, t-test, F-test, coefficient of determination (Adjusted R²), and standardized beta coefficients. The results show that location, facilities, and service quality each have a positive and significant effect on guest satisfaction. Partially, location contributes significantly despite some accessibility limitations. Facilities also have a significant effect, indicating the importance of adequate physical amenities in supporting guest comfort. Among the three variables, service quality is the most dominant factor influencing guest satisfaction, as indicated by the highest standardized beta coefficient. Simultaneously, all independent variables significantly affect guest satisfaction, with an adjusted R² value of 0.696, meaning that 69.6% of the variation in guest satisfaction is explained by the model. These findings highlight the importance of improving service quality, enhancing facilities, and addressing location-related issues to increase guest satisfaction.